Preparation method and application of FeOOH-green algae active cell composite gel ball adsorption material embedded in sodium alginate

The FeOOH-green algae active cell composite gel beads adsorption material embedded in sodium alginate solves the problem of difficulty in efficiently removing MG-containing wastewater in the existing technology, achieves a synergistic effect of efficient adsorption and biodegradation, and improves the efficiency of adsorption. Treatment efficiency of organic pollutants.

CN116272885BActive Publication Date: 2025-01-21YANGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310149161.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-20
Publication Date
2025-01-21
Estimated Expiration
2043-02-20

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove industrial wastewater containing malachite green (MG), and traditional adsorbent materials are inefficient and costly when treating organic polluted liquids, and it is difficult to achieve the synergistic effect of adsorption and biodegradation.

Method used

The FeOOH-green algae active cell composite gel pellet adsorption material embedded in sodium alginate is used to evenly distribute the green algae cells and FeOOH particles in the sodium alginate gel to form a pellet-shaped adsorption material. The algae cells and The adsorption and biodegradation capabilities of FeOOH particles improve the adsorption efficiency of organic pollutants.

Benefits of technology

It achieves efficient removal of malachite green dye, improves the adsorption capacity and removal rate of organic pollutants, and the material does not require the addition of pore-forming agents and high-temperature roasting. The preparation method is simple, the energy consumption is low, and it has high research value and application advantages. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116272885B_ABST
    Figure CN116272885B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a FeOOH-green algae active cell composite gel ball adsorption material embedded in sodium alginate, wherein sodium alginate and a certain concentration of green algae liquid are mixed, and then added dropwise to a Fecl3 solution to form a gel ball. The ball is then left to stand for a period of time to age, and then taken out and repeatedly rinsed with deionized water for several times before use. The Fecl3-green algae gel ball embedded in sodium alginate provided by the invention has the advantages of simple preparation process and low cost, and stable structure, low energy consumption, good treatment effect, wide application range, etc., and has high research value and application advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method and application of a sodium alginate-embedded FeOOH-green algae active cell composite gel ball adsorption material, belonging to the technical field of water treatment. Background Art

[0002] Rapid industrial development has led to a demand for wastewater treatment. As an important industrial raw material, organic dyes are widely used in the paper, textile and plastic industries. Some organic dyes are highly toxic and difficult to degrade, and can be discharged into the natural environment with industrial wastewater, causing serious water pollution and threatening the health of aquatic organisms and humans. Malachite green (MG) is highly cytotoxic to mammalian cells and has adverse effects on the liver, gills, kidneys, intestines, gonads and pituitary gonadotropins. In addition, it may enter the food chain and may have carcinogenic, mutagenic and teratogenic effects in humans. Although MG has been banned in some countries, it is still used in many countries around the world due to its low cost, good availability, good efficacy and lack of suitable alternative drugs. Therefore, it is crucial to treat wastewater contaminated with MG before it is discharged into the environment.

[0003] There have been studies on the removal of dyes from wastewater by a number of physical, chemical and biological methods. The most common methods include ion exchange, adsorption, membrane separation and photodegradation. Currently, adsorption is considered to be one of the most effective methods for removing dyes from aqueous solutions. This method has attracted much attention because of its high efficiency, economy, simplicity and lack of secondary pollution. The selection of adsorbent materials with appropriate properties is important for the precise regulation of the adsorption behavior.

[0004] As the eutrophication of water bodies increases, a large number of algae proliferate, seriously affecting the water quality and promoting the development and research of algae application technology. Algae have a large specific surface area and rich functional groups on the surface of their cell walls, such as amino, hydroxyl, carboxyl, etc. Some pollutants in wastewater can be removed by bonding with these functional groups or undergoing electrical adsorption. Summary of the invention

[0005] The purpose of the present invention is to solve the above problems and to provide a preparation method and application of a FeOOH-green algae active cell composite gel ball adsorption material embedded with sodium alginate.

[0006] The object of the present invention is achieved by: a method for preparing a sodium alginate-embedded FeOOH-green algae active cell composite gel sphere adsorption material, characterized in that it comprises the following steps:

[0007] (1) The green algae liquid is centrifuged, and then the supernatant is discarded to collect the algae cells, and BG11 medium (a commonly used culture medium for freshwater blue algae and green algae) is added to wash once, and the washed algae liquid is allowed to stand for 15-20 minutes to allow the algae cells to stabilize in the culture medium;

[0008] (2) Counting the algae cells in the cleaned algae solution using an optical microscope to determine the algae cell concentration;

[0009] (3) Take 50 ml of the algae solution containing green algae cells in step (2) and add 1.0 g of sodium alginate powder; stir evenly using a stirrer to ensure that the algae cells are evenly distributed in the sodium alginate gel;

[0010] (4) centrifuging the sodium alginate gel containing green algae cells to expel the air inside the gel;

[0011] (5) Prepare FeCl3 solution with deionized water;

[0012] (6) slowly dripping the mixed solution prepared in step (3) into the solution in step (4) using an injection to form small spherical balls;

[0013] (7) adding NaOH to the solution in step (4), ultrasonically treating the pellets for 10 min, and allowing them to stand for 6 h to age, so that FeOOH particles are generated in the gel, enriching organic matter, promoting the adsorption of organic matter, and enhancing biodegradation;

[0014] (8) The solidified gel beads are filtered out with a net bag, and washed with deionized water for 2-3 times to remove free iron ions on the surface; the obtained gel beads are FeOOH-green algae active cell composite gel beads adsorption materials embedded in sodium alginate.

[0015] In step (1), the BG11 culture medium is prepared by adding 0.7 g of BG11 powder to 1000 ml of distilled water, heating the culture medium in a constant temperature water pot at 80° C. for 2 h, and then sterilizing the heated culture medium; BG11 culture medium is a culture medium for freshwater cyanobacteria and green algae.

[0016] In step (2), the number of algae cells in the green algae solution is 1×10 6 —1×10 7 Pieces / ml.

[0017] In step (3), the concentration of the sodium alginate solution is 2 w / v%.

[0018] In step (5), the concentration of the FeCl3 solution is 0.1 mol / L.

[0019] In step (1) and step (4), during the centrifugal treatment, the centrifugal speed is 3600 rpm / min.

[0020] In step (6), the specification of the injection is 2.5 ml of injection; the diameter of the pellet is 2-3 mm.

[0021] A sodium alginate-embedded FeOOH-green algae active cell composite gel is used in malachite green dye wastewater containing cations.

[0022] The method of the present invention is advanced and scientific. Through the present invention, the purpose of the present invention is to provide a sodium alginate-embedded Fecl3-green algae gel bead adsorption material on the one hand, and the preparation method and application of the bead on the other hand. The sodium alginate-embedded Fecl3-green algae gel bead of the present invention is made by cross-linking sodium alginate, green algae, deionized water and Fecl3, wherein sodium alginate is an embedding agent and Fecl3 is a cross-linking agent. The extracellular polymer (EPS) of algae is mainly composed of polysaccharides and humus substances, and they are rich in negatively charged groups such as carboxyl and hydroxyl groups, so they have strong metal complexing ability and can form FeooH with iron. FeOOH adsorbs organic matter in the hydrogel pores through ion and ligand exchange, dipole force and hydrogen bond force. And the FeOOH on the surface of the active algae cells plays a role in enhancing the mass transfer of organic matter to the adsorption site due to the confinement effect in the narrow space of the gel pores, thereby enhancing the adsorption and biodegradation of organic matter by green algae. Finally, the adsorption capacity of the composite beads on organic matter is comprehensively improved. The whole system prepared by this method can achieve the synergistic effect of adsorption and biodegradation.

[0023] The Fecl3-green algae gel bead adsorption material embedded in sodium alginate provided by the present invention can not only utilize the green algae that originally affects the water quality, but also give full play to its adsorption to organic polluted liquid. And it can be embedded and reused, reducing the impact of hydraulic migration on the green algae. In addition, the Fecl3-green algae gel bead adsorption material embedded in sodium alginate prepared by the present invention does not need to add pore-forming agents, nor does it need high-temperature roasting. The preparation method is simple, and it has the advantages of low energy consumption, good treatment effect, wide application range, low cost, etc. It improves the separation of the adsorbent and the polluted liquid and the problem of reusing the adsorbent, and has high research value and unique application advantages.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. Raw material Fecl of the present invention 3、 Green algae and sodium alginate are widely available, and their preparation methods are simple, economical and fast.

[0026] 2. The FeOOH-green algae active cell composite gel ball adsorption material embedded in sodium alginate provided by the present invention can not only utilize the green algae that originally affects the water quality, but also give full play to its adsorption of organic pollutant liquid. Moreover, it can be embedded and reused, reducing the impact of hydraulic migration on the green algae.

[0027] 3. The sodium alginate-embedded FeOOH-green algae active cell composite gel bead adsorption material prepared by the present invention does not require the addition of pore-forming agents or high-temperature calcination, has a simple preparation method, and has the advantages of low energy consumption, good treatment effect, wide application range, low cost, etc., and has high research value and unique application advantages.

[0028] 4. The sodium alginate-encapsulated FeOOH-green algae active cell composite gel bead adsorption material has strong adsorption ability, good removal rate and high adsorption capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The FeOOH-green algae active cell composite gel ball adsorption material embedded with sodium alginate prepared in Example 1 of the present invention;

[0030] Figure 2 The internal structure of the FeOOH-green algae active cell composite gel sphere embedded with sodium alginate prepared in Example 1 under a microscope, it can be seen that the green algae cells are evenly wrapped inside the gel sphere;

[0031] Figure 3 This is a performance diagram of the high-efficiency adsorption beads prepared by the present invention for removing organic pollutants;

[0032] Figure 4 This is a graph showing the adsorption performance of the high-efficiency adsorption beads prepared by the present invention for organic polluted liquids at different pH values;

[0033] Figure 5 This is a diagram showing the adsorption performance of the high-efficiency adsorption beads prepared for the invention in organic polluted liquids of different concentrations. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below in conjunction with the embodiments and drawings.

[0035] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents described are commercially available unless otherwise specified.

[0036] Example 1

[0037] The specific steps of preparing the FeCl3-chlorella gel beads adsorption material embedded with sodium alginate in this embodiment are as follows:

[0038] (1) Centrifuge the green algae solution (3600 rpm / min), then discard the supernatant to collect the algae cells, and add BG11 (a commonly used culture medium for freshwater cyanobacteria and green algae) to wash once. Let the washed algae solution stand for 15-20 minutes to allow the algae cells to stabilize in the culture medium.

[0039] (2) Use an optical microscope to count the algal cells in the cleaned algal solution and control the algal cell concentration to 1×10 6 Pieces / ml.

[0040] (3) Weigh 1.0 g of sodium alginate powder and put it into 50 ml of the algae cell concentration in step (2) to 1×10 6 The algae cells were evenly distributed in the sodium alginate gel.

[0041] (4) centrifuging the sodium alginate gel containing green algae cells (3600 rpm / min) to expel the air inside the gel;

[0042] (5) Weigh 1.625 g of Fecl3, add it to 100 ml of deionized water and stir evenly (the mass concentration of Fecl3 solution is 0.1 mol / L).

[0043] (6) Use a 2.5 ml injection to slowly drip the mixed solution prepared in step (3) into the FeCl3 solution in step (4) to form small spheres. The diameter of the gel spheres containing algae cells is 2-3 mm.

[0044] (7) NaOH is added to the pellets in the solution prepared in step (4), and the pellets are subjected to ultrasonic treatment for 10 min, and then allowed to stand for 6 h for aging (to generate FeOOH particles in the gel, enrich organic matter, promote the adsorption of organic matter, and enhance biodegradation).

[0045] (8) The solidified gel beads are filtered out using a net bag and washed with deionized water for 2-3 times to remove the free iron ions on the surface. The obtained gel beads are FeOOH-green algae active cell composite gel beads adsorption materials embedded in sodium alginate, and the morphology is as follows: Figure 1 shown.

[0046] Example 2

[0047] The specific steps of preparing the FeOOH-green algae active cell composite gel sphere adsorption material embedded with sodium alginate in this embodiment are as follows:

[0048] (1) Centrifuge the green algae solution (3600 rpm / min), then discard the supernatant to collect the algae cells, and add BG11 (a commonly used culture medium for freshwater cyanobacteria and green algae) to wash once. Let the washed algae solution stand for 15-20 minutes to allow the algae cells to stabilize in the culture medium.

[0049] (2) Use an optical microscope to count the algal cells in the cleaned algal solution and control the algal cell concentration to 5×10 6 Pieces / ml.

[0050] (3) Weigh 1.0 g of sodium alginate powder and put it into 50 ml of the algae cell concentration in step (2) to 5 × 10 6 The algae cells were evenly distributed in the sodium alginate gel.

[0051] (4) centrifuging the sodium alginate gel containing green algae cells (3600 rpm / min) to expel the air inside the gel;

[0052] (5) Weigh 1.625 g of Fecl3, add it to 100 ml of deionized water and stir evenly (the mass concentration of Fecl3 solution is 0.1 mol / L).

[0053] (6) Use an injection to slowly drip the mixed solution prepared in step (3) into the FeCl3 solution in step (4) to form small spheres. The diameter of the gel spheres containing algae cells is 2-3 mm.

[0054] (7) NaOH is added to the pellets in the solution prepared in step (4), and the pellets are subjected to ultrasonic treatment for 10 min, and then allowed to stand for 6 h for aging (to generate FeOOH particles in the gel, enrich organic matter, promote the adsorption of organic matter, and enhance biodegradation).

[0055] (8) The solidified gel beads are filtered out using a net bag and washed with deionized water for 2-3 times to remove the free iron ions on the surface. The obtained gel beads are FeOOH-green algae active cell composite gel beads adsorption materials embedded in sodium alginate, and the morphology is as follows: Figure 1 shown.

[0056] Example 3

[0057] The specific steps of preparing the FeOOH-green algae active cell composite gel beads adsorption material embedded with sodium alginate in this embodiment are as follows:

[0058] (1) Centrifuge the green algae solution (3600 rpm / min), then discard the supernatant to collect the algae cells, and add BG11 (a commonly used culture medium for freshwater cyanobacteria and green algae) to wash once. Let the washed algae solution stand for 15-20 minutes to allow the algae cells to stabilize in the culture medium.

[0059] (2) Use an optical microscope to count the algal cells in the cleaned algal solution and control the algal cell concentration to 1×10 7 Pieces / ml.

[0060] (3) Weigh 1.0 g of sodium alginate powder and put it into 50 ml of the algae cell concentration in step (2) to 1×10 7 The algae cells were evenly distributed in the sodium alginate gel.

[0061] (4) centrifuging the sodium alginate gel containing green algae cells (3600 rpm / min) to expel the air inside the gel;

[0062] (5) Weigh 1.625 g of Fecl3, add it to 100 ml of deionized water and stir evenly (the mass concentration of Fecl3 solution is 0.1 mol / L).

[0063] (6) Use an injection to slowly drip the mixed solution prepared in step (3) into the FeCl3 solution in step (4) to form small spheres. The diameter of the gel spheres containing algae cells is 2-3 mm.

[0064] (7) NaOH is added to the pellets in the solution prepared in step (4), and the pellets are subjected to ultrasonic treatment for 10 min, and then allowed to stand for 6 h for aging (to generate FeOOH particles in the gel, enrich organic matter, promote the adsorption of organic matter, and enhance biodegradation).

[0065] (8) The solidified gel beads are filtered out using a net bag and washed with deionized water for 2-3 times to remove the free iron ions on the surface. The obtained gel beads are FeOOH-green algae active cell composite gel beads adsorption materials embedded in sodium alginate, and the morphology is as follows: Figure 1 shown.

[0066] Example 4

[0067] The specific steps for preparing gel beads containing only sodium alginate in this embodiment are:

[0068] Weigh 1.0 g of sodium alginate powder and add it to 50 ml of deionized water (the concentration of the sodium alginate gel solution is 2 w / v%). Stir evenly with a stirrer.

[0069] The sodium alginate gel was centrifuged (3600 rpm / min) to expel the air inside the gel;

[0070] (3) Weigh 1.625 g of Fecl3, add it to 100 ml of deionized water and stir evenly (the mass concentration of Fecl3 solution is 0.1 mol / L).

[0071] (4) Use an injection to slowly drip the mixed solution prepared in step (1) into the FeCl3 solution in step (2) to form small spheres. The diameter of the gel spheres should be 2-3 mm.

[0072] (5) NaOH is added to the pellets in the solution prepared in step (3), and the pellets are subjected to ultrasonic treatment for 10 min, and then allowed to stand for 6 h for aging (to generate FeOOH particles in the gel, enrich organic matter, promote the adsorption of organic matter, and enhance biodegradation).

[0073] (6) The solidified gel beads are filtered out using a net bag to obtain the gel beads, i.e., FeCl3 gel beads adsorption materials embedded in sodium alginate.

[0074] Example 5

[0075] Evaluation of the performance of the gel beads prepared in Examples 1-5 above in removing organic pollutants.

[0076] An MG solution with an initial concentration of 50 mg / L was prepared to simulate organic polluted liquid wastewater, and the gel beads prepared in Examples 1-5 were added respectively. Under the conditions of a solid-liquid ratio of 1:2 and a temperature of 25° C., an adsorption experiment was carried out with a magnetic stirrer for 24 hours.

[0077] An MG solution with an initial concentration of 50 mg / L was prepared to simulate organic polluted liquid wastewater, and the gel beads prepared in Example 1 were added, and the pH values ​​were adjusted to 3, 4, and 5. Under the conditions of a solid-liquid ratio of 1:2 and a temperature of 25°C, an adsorption experiment was carried out with a magnetic stirrer for 24 hours.

[0078] MG solutions with concentrations of 50 mg / L, 75 mg / L, and 100 mg / L were prepared to simulate organic polluted liquid wastewater, and the gel beads prepared in Example 1 were added. Under the conditions of a solid-liquid ratio of 1:2 and a temperature of 25°C, an adsorption experiment was carried out with a magnetic stirrer for 24 hours.

[0079] After the experiment, the removal rate of organic polluted liquid and the adsorption amount of gel beads were calculated.

[0080] Removal rate calculation formula:

[0081] In formula (1), η is the removal rate (%); C0, C e—The initial concentration of MG before treatment and the concentration of MG after treatment (mg / L). Adsorption capacity calculation formula

[0082] In formula (2), Q e —Adsorption capacity, mg / g; C0, C e —MG initial concentration before treatment and concentration after treatment (mg / L); V-solution volume, L; m-green algae encapsulation amount, g.

[0083] Calculation of the amount of green algae to be embedded: Take 50 ml of the green algae solution from the same batch of culture, filter it with filter paper, put it in an oven at 60°C for 48 hours, and weigh it after drying.

[0084] Experimental results:

[0085] like Figure 3 As shown in the figure, A represents the adsorption curve of the gel beads prepared in Example 1, B represents the adsorption curve of the gel beads prepared in Example 2, C represents the adsorption curve of the gel beads prepared in Example 3, and D represents the adsorption curve of the gel beads prepared in Example 4. Figure 2 It can be seen that: (1) the adsorption effect of the gel beads embedded with green algae is much better than that of the gel beads without green algae; (2) the optimal formula is that the algae concentration is 1×10 7 When the organic dye removal rate reached 86.24% in 24 hours, the adsorption capacity reached 47.8 mg / g.

[0086] like Figure 4 As shown in the figure, A represents the adsorption curve of the gel beads prepared in Example 1 in the contaminated liquid with a pH of 3, B represents the adsorption curve of the gel beads prepared in Example 1 in the contaminated liquid with a pH of 4, and C represents the adsorption curve of the gel beads prepared in Example 1 in the contaminated liquid with a pH of 5. Figure 3 It can be seen that the FeOOH-green algae active cell composite gel beads have a better adsorption effect in acidic pollution.

[0087] like Figure 5 As shown in the figure, A represents the adsorption curve of the gel beads prepared in Example 1 in the contaminated liquid with MG of 50 mg / mL, B represents the adsorption curve of the gel beads prepared in Example 1 in the contaminated liquid with MG of 75 mg / mL, and C represents the adsorption curve of the gel beads prepared in Example 1 in the contaminated liquid with MG of 100 mg / mL. Figure 4 It can be seen that the FeOOH-green algae active cell composite gel beads have a good adsorption effect in 50-100 mg / mL MG organic pollution.

[0088] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a sodium alginate-embedded FeOOH-green algae active cell composite gel sphere adsorption material, characterized in that: The following steps are involved: (1) Centrifuge the green algae solution, then discard the supernatant to collect the algae cells, add BG11 culture medium to wash, and let the washed algae solution stand for 15-20 minutes to allow the algae cells to stabilize in the culture medium; (2) Count the algal cells in the cleaned algal solution using an optical microscope to determine the algal cell concentration; (3) Take 50 ml of the algae solution containing green algae cells in step (2) and add 1.0 g of sodium alginate powder; stir evenly using a stirrer to ensure that the algae cells are evenly distributed in the sodium alginate gel; (4) centrifuging the sodium alginate gel containing green algae cells to expel the air inside the gel; (5) Prepare FeCl3 solution with deionized water; (6) Using an injection device, slowly drip the mixed solution prepared in step (3) into the solution in step (5) to form small spherical balls; (7) NaOH is added to the solution in step (5), and the pellets are subjected to ultrasonic treatment for 10 min, and allowed to stand for 6 h for aging, so that FeOOH particles are generated in the gel, which enriches organic matter, promotes the adsorption of organic matter, and enhances biodegradation; (8) Filtering the solidified gel beads with a net bag, washing them with deionized water for 2-3 times to remove free iron ions on the surface; the obtained gel beads are FeOOH-green algae active cell composite gel beads adsorption materials embedded in sodium alginate; In step (5), the concentration of the FeCl3 solution is 0.1 mol / L.

2. The method for preparing a sodium alginate-embedded FeOOH-green algae active cell composite gel bead adsorption material according to claim 1, characterized in that: In step (1), the BG11 culture medium is prepared by adding 0.7 g of BG11 powder to 1000 ml of distilled water, heating the culture medium in a constant temperature water bath at 80°C for 2 h, and then sterilizing the culture medium.

3. The method for preparing a sodium alginate-embedded FeOOH-green algae active cell composite gel bead adsorption material according to claim 1, characterized in that: In step (2), the number of algal cells in the washed algal solution is 1×10 6 —1×10 7 Pieces / ml.

4. The method for preparing a sodium alginate-embedded FeOOH-green algae active cell composite gel bead adsorption material according to claim 1, characterized in that: In step (1) and step (4), during the centrifugation treatment, the centrifugal speed is 3600 rpm / min.

5. The method for preparing a sodium alginate-embedded FeOOH-green algae active cell composite gel bead adsorption material according to claim 1, characterized in that: In step (6), the specification of the injection is 2.5 ml of injection; the diameter of the pellet is 2-3 mm.

6. Use of a sodium alginate-embedded FeOOH-green algae active cell composite gel bead adsorption material obtained by the preparation method according to any one of claims 1 to 5 in cationic malachite green dye wastewater.

Citation Information

Patent Citations

  • Deep nitrogen and phosphorus removal compound microalgae and preparation method and application thereof

    CN109437409A